2020
DOI: 10.1002/ajb2.1426
|View full text |Cite
|
Sign up to set email alerts
|

The soil microbial community alters patterns of selection on flowering time and fitness‐related traits in Ipomoea purpurea

Abstract: Premise Plant flowering time plays an important role in plant fitness and thus evolutionary processes. Soil microbial communities are diverse and have a large impact, both positive and negative, on the host plant. However, owing to few available studies, how the soil microbial community may influence the evolutionary response of plant populations is not well understood. Here we sought to uncover whether belowground microbial communities act as an agent of selection on flowering and growth traits in the common … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
(76 reference statements)
1
32
0
Order By: Relevance
“…However, it is unknown whether the same traits are involved in shaping the maize microbiome. An additional complication is the fact that the microbiome can, in turn, affect phenotypic expression in the host plant (Panke‐Buisse et al ., 2017; Berg & Koskella, 2018; O’Brien et al ., 2019) as well as the relationship between phenotype and yield (Wagner et al ., 2014; Chaney & Baucom, 2020). For these reasons, careful experimentation – not just simultaneous measurement of plant traits and microbiome features – will be needed to clarify the phenotypic links between heterozygosity and microbiome heterosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether the same traits are involved in shaping the maize microbiome. An additional complication is the fact that the microbiome can, in turn, affect phenotypic expression in the host plant (Panke‐Buisse et al ., 2017; Berg & Koskella, 2018; O’Brien et al ., 2019) as well as the relationship between phenotype and yield (Wagner et al ., 2014; Chaney & Baucom, 2020). For these reasons, careful experimentation – not just simultaneous measurement of plant traits and microbiome features – will be needed to clarify the phenotypic links between heterozygosity and microbiome heterosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our reciprocal transplants revealed that serpentine microorganisms, when in non-serpentine soils, accelerate vegetative, early flowering, and flowering phenology (Table 4). The importance of the microbial community for time to flowering has been previously demonstrated in Arabidopsis (Wagner et al 2014) and Ipomea purpurea (Chaney and Baucom 2020). Drought-adapted microbes accelerated flowering in Brassica when compared to non-drought-adapted microbes (Lau and Lennon 2012).…”
Section: Discussionmentioning
confidence: 88%
“…One way in which determining whether and how environmental microbial communities may mitigate plant adaptation is by determining whether such communities act as a selective agent on important plant traits. Chaney and Baucom (2020) show this to be the case by autoclaving soil to modify the soil microbial community. Doing so altered the pattern of selection on growth and flowering phenology in the common morning glory, Ipomoea purpurea, compared to plants growing in intact soils.…”
Section: Living Togethermentioning
confidence: 88%